Compellability of Muslim witnesses in the Syariah Courts in Malaysia: is non-Muslim also included? - Kamarudin, Abdul Rani; Arinen, Ahadin; Md. Dahlan, Nuarrual Hilal (IIUM Press, 2009)
This paper discusses the importance and the instrumental role of witnesses in the States' of Malaysia Islamic administration of justice, particularly the Syariah Courts in Malaysia. Can a witness who refuses to attend a court hearing to give evidence after being duly summon may be compelled by a warrant of arrest to do so? Accordingly, this paper looks at the laws in the Federal Constitution, Criminal Procedure Code, the law of evidence and selected States' Islamic laws Enactments in Malaysia pertaining to the obligation of a witness to come forward to the court to give evidence as being necessary in expediting the administration of justice. This paper will also highlight some measures necessary to be taken into consideration by the Syariah Courts before invoking any action to compel the attendance of a witness to testify in court or when instituting contempt proceeding against a 'rebellious' witness. This paper will also explain why the obligation to give evidence in the Syariah Courts covers non-Muslim witnesses as well.